Pengaruh Kualitas Pelayanan dan Sarana Pendukung Pelayanan Terhadap Kepuasan Nasabah Dalam Masa Pandemi COVID 19 - Nora Nurmayanti; Annaria Magdalena Marpaung (Jurnal Ilmiah Manajemen Kesatuan, 2022)
This study aims to determine the effect of service quality and service support facilitieson customer satisfaction during the COVID-19 pandemic. The purpose of this study is toexamine the effect of service quality and supporting facilities on customer satisfactionof Bank BRI and Bank BNI. The population used in this study were customers of Bank BNI and Bank BRI. The samplein this study were 100 respondents and used Non Probability Sampling technique. Theanalytical method used is quantitative analysis, namely multiple regression analysis.This analysis includes validation test and reliability test, multiple regression analysis, t test, f test, analysis of the coefficient of determination (R2) and correlation analysis. Based on the results of the T test, the Service Quality variable (X1) has a positiveinfluence on customer satisfaction (Y) while the Service Support Facility variable (X2)does not have a positive influence on Customer Satisfaction (Y). Based on the F test, itcan be seen that the Service Quality variable (X1) and the Service Support Facility (X2)variable simultaneously have a positive effect on Customer Satisfaction (Y). Adjusted Rsquare shows that 18.8% variation of Customer Satisfaction can be explained by thetwo independent variables in the multiple regression equation. While the rest isexplained by other variables outside the two variables. Keywords: Service Quality, Service Support Facilities, Customer Satisfaction